Suspension Bridge Estimation Method using the Fokker-Planck Model - Jufriansah, Adi; Lazwardi, Ahmad; Pramudya, Yudhiakto; Nurrahman, Arip; Khusnani, Azmi; Yohakim, Yoman Ribeta Ratu (Journal of Novel Engineering Science and Technology, 2024)
The failure of the suspension bridge has been known since the beginning of the bridge collapse. Most of these failures form the basis of current engineering knowledge. One of the factors of failure is human-made factors related to the calculation of the bridge estimate. This paper presents an indirect estimation method using numerical simulation using finite elements by analyzing the Fokker-Planck model when dynamic excitation is associated with bridge loads. The results show that the Fokker-Planck model's homogeneous form can take into account the solution for the bridge analysis approach. It leads to a stable state when giving mass variations to the model. The indirect estimation method using finite elements can estimate the cable tension with controllable weak damping. It can be concluded that the method in this study is more accurate and convenient for the application technique.